2003
DOI: 10.1523/jneurosci.23-32-10265.2003
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Rewarding Properties of Morphine, but not Cocaine, in βarrestin-2 Knock-Out Mice

Abstract: The reinforcing and psychomotor effects of morphine involve opiate stimulation of the dopaminergic system via activation of mu-opioid receptors (muOR). Both mu-opioid and dopamine receptors are members of the G-protein-coupled receptor (GPCR) family of proteins. GPCRs are known to undergo desensitization involving phosphorylation of the receptor and the subsequent binding of beta(arrestins), which prevents further receptor-G-protein coupling. Mice lacking beta(arrestin)-2 (beta(arr2)) display enhanced sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
233
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(263 citation statements)
references
References 51 publications
25
233
5
Order By: Relevance
“…Although others have found that sensitization to morphine is not b-arrestin 2-dependent (Bohn et al, 2003), we have found that this context-specific response to multiple doses of morphine is reduced in mice lacking b-arrestin 2. However, our assay differed in several important ways; we examined the first 30 min after morphine (30 vs 120 min), after 3 rather than 9 days of repeated morphine, and our sensitization protocol was context-associated.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Although others have found that sensitization to morphine is not b-arrestin 2-dependent (Bohn et al, 2003), we have found that this context-specific response to multiple doses of morphine is reduced in mice lacking b-arrestin 2. However, our assay differed in several important ways; we examined the first 30 min after morphine (30 vs 120 min), after 3 rather than 9 days of repeated morphine, and our sensitization protocol was context-associated.…”
Section: Discussioncontrasting
confidence: 94%
“…This response requires D1 receptors, the phosphoprotein DARPP32 (Becker et al, 2001;Borgkvist et al, 2007;Urs et al, 2011) and ERK (Borgkvist et al, 2008;Urs et al, 2011). We, and others, have shown that the locomotor effect of morphine is blunted in mice lacking b-arrestin 2 (Bohn et al, 2003;Urs et al, 2011). As morphine induces the formation of a b-arrestin 2/ERK complex in D1 neurons, it has been suggested that this complex mediates the hyperlocomotor effect of morphine (Urs et al, 2011).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…MEF trafficking. MEF cells were transiently transfected with 2-2.5 g of 5-HT2AR-YFP cDNA by using the Gene Pulser Xcell electroporation system as described previously (Bio-Rad) (36). Images presented are representative of at least four separate transfections and drug treatments.…”
Section: Discussionmentioning
confidence: 99%
“…20 Briefly, the CPP procedure consisted of day 1 of preconditioning (pretest), where the mice were allowed to freely move between all chambers of the CPP apparatus and the time spent (basal preference) in each chamber was recorded for 30 min. In the conditioning phase, the mice were injected with morphine (3 or 6 mg kg À1 ) on days 2, 4 and 6 and Sal on days 3, 5 and 7, and the drug was randomly paired with alternating compartments, such that half of the mice received drug in the black compartment and the other half in the white compartment.…”
Section: Conditioned Place Preferencementioning
confidence: 99%